Social predictors of HIV-testing among Malaysian individuals at higher risk of HIV infection - Mehrabi, Davood; Tamam, Ezhar; Hasan, Hamisah; Bolong, Jusang (Science Publishing Group, 2021)
Willingness to test for HIV is initial critical factor to break HIV transmission cycle. This study determined social predictors of willingness for HIV-testing among Malaysians at higher risk of HIV infection. A cross-sectional survey involving 369 individuals at higher risk of HIV was conducted in the Klang Valley, Malaysia. The study used a combination of snowball and respondent-driven sampling methods to approach 456 individuals yielded a response rate of 80.9%. Data were analysed using logistic regression. Almost one third (35.2%) of the respondents were willing to test for HIV. The odd ratios suggest that the odds of estimating correctly who is willing to take HIV-testing improve by 89% if one knows the subject’s level of HIV-related self-stigma, by 11% if one knows the subject’s level of HIV knowledge, and by 6% if one knows the subject’s age. Successful intervention programs to increase HIV testing willingness among individuals at higher risk of HIV infection is contingent upon the subjects’ HIV-related self-stigma, knowledge about HIV and age. The role of HIV-related self-stigma is more prominent to prevent individual at higher risk of HIV exposure from HIV testing. Further research is needed to investigate social context-specific predictors of HIV-related self-stigma.